Improvement of technological processes for mining solid mineral resources - Novak, Anatolii; Fesenko, Eduard; Pavlov, Yevhen (Technology audit and production reserves, 2021)
The object of research is the technological processes of the development of deposits and the extraction of solid minerals by underground and open-pit methods. The improvement of technological processes is achieved through the use of existing original technical solutions, which are currently advisable to use in practice. The work is aimed at increasing the efficiency of explosive energy use, improving the technological processes of mining operations in coal mines and open pits of mining enterprises. In the course of the study, an analysis of technical literature on mining topics was used, a search for copyright certificates for inventions and patents on the same topic was carried out. There was a search for innovative solutions that are expedient to apply at the present time. In the course of the analysis, the work shows ideas, methods of coal mining, systems for the development of coal seams, methods of destruction of rocks, microbiological reclamation and other new technologies and devices. The most promising technologies have been proposed for in-depth study, implementation and use in appropriate mining and geological conditions. The proposed technologies, for various reasons, have not yet found wide practical application at mining enterprises. Due to the application of the proposed technical solutions and technologies in practice in the conditions of existing coal mines and open pits, significant economic, environmental and financial effects can be obtained. This study was carried out in order to bring to a wide circle of specialists technical solutions that can contribute to a significant improvement in the technology of mining solid minerals, both in underground and open-pit mining all over the world.